Mushroom diversity in the Sagarmatha national park and its buffer zone area - Rana, Prabina; Giri, Anjana (Banko Janakari, 2008)
Nepal is rich in mycodiversity. However, only a few scientific researches have been conducted. It has been observed that mycological studies are concentrated to lower altitude as compared to higher altitude. This paper aims to document the wild mushrooms and its diversity in the Khumbu region. A total of 150 mushroom species belonging to 37 families and 65 genera were collected from Lukla (2480m above msl) to Panboche (4000m above msl). The largest family recorded were Boletaceae and Russulaceae having 18 species followed by Tricholomataceae (16 sps.), Polyporaceae (9 sps) etc. Most of the collected mushroom species were found on soil. The appearance, occurrence and dominance were found to be controlled by different factors such as altitude, vegetation, temperature, humidity, etc. the diversity of mushroom species were found the highest (84 sps.) at an altitudinal range of 3500 – 4000m above msl followed by 2500 – 3000m above msl (52 sps.) and 3000 – 3500m above msl (14 sps.).Key words: Mycodiversity; vegetation; habitat; dominant; Khumbu regionBanko Janakari Vol.16(2) 2006 pp.17-24